Price setting in online markets: Does IT click? - Yuriy Gorodnichenko; Viacheslav Sheremirov; Oleksandr Talavera (Federal Reserve Bank of Boston, 2015)
Using a unique dataset of daily U.S. and U.K. price listings and the associated number of clicks for precisely defined goods from a major shopping platform, we shed new light on how prices are set in online markets, which have a number of special properties such as low search costs, low costs of monitoring competitors' prices, and low costs of nominal price adjustment. We document that although online prices are more flexible than offline prices, they nevertheless exhibit relatively long spells of fixed prices, large size, and low synchronization of price changes, considerable crosssectional dispersion, and low sensitivity to predictable or unanticipated changes in demand conditions. Qualitatively, these patterns are similar to those observed for offline prices, a finding that suggests a need for more research on the sources of price rigidities and dispersion.
Keywords: E3; 330; online markets; prices; price dispersion